Cholesterol Efflux-Independent Modification of Lipid Rafts by AIBP (Apolipoprotein A-I Binding Protein). Issue 10 (October 2020) - Low, Hann; Mukhamedova, Nigora; Capettini, Luciano dos Santos Aggum; Xia, Yining; Carmichael, Irena; Cody, Stephen H.; Huynh, Kevin; Ditiatkovski, Michael; Ohkawa, Ryunosuke; Bukrinsky, Michael; Meikle, Peter J.; Choi, Soo-Ho; et al.
Abstract : Objective: AIBP (apolipoprotein A-I binding protein) is an effective and selective regulator of lipid rafts modulating many metabolic pathways originating from the rafts, including inflammation. The mechanism of action was suggested to involve stimulation by AIBP of cholesterol efflux, depleting rafts of cholesterol, which is essential for lipid raft integrity. Here we describe a different mechanism contributing to the regulation of lipid rafts by AIBP. Approach and Results: We demonstrate that modulation of rafts by AIBP may not exclusively depend on the rate of cholesterol efflux or presence of the key regulator of the efflux, ABCA1 (ATP-binding cassette transporter A-I). AIBP interacted with phosphatidylinositol 3-phosphate, which was associated with increased abundance and activation of Cdc42 and rearrangement of the actin cytoskeleton. Cytoskeleton rearrangement was accompanied with reduction of the abundance of lipid rafts, without significant changes in the lipid composition of the rafts. The interaction of AIBP with phosphatidylinositol 3-phosphate was blocked by AIBP substrate, NADPH (nicotinamide adenine dinucleotide phosphate), and both NADPH and silencing of Cdc42 interfered with the ability of AIBP to regulate lipid rafts and cholesterol efflux. Conclusions: Our findings indicate that an underlying mechanism of regulation of lipid rafts by AIBP involves PIP-dependent rearrangement of the cytoskeleton. Abstract : Supplemental Digital Content is available in the text.